Postur Kifosis Menyebabkan Gangguan Keseimbangan Statis Lansia - Rema Ira Prastiwi; Riska Risty W; Sri Lestari (Poltekkes Kemenkes Surakarta, 2020)
Background: Elderly is someone who has body functions deficiency both physically and psychologically. One of the physical function deficiencies is the decrease in musculoskeletal conditions that affects the balance of postural muscles which results in the changes of kyphosis posture, so that it affects the changes of the body's center of gravity (COG) toward the fulcrum which causes disturbance of static balance. This poor static balance creates the risk of falling which causes many problems and even death for the elderly. Aims of this study to determine the correlation between changes in kyphosis posture and static balance disorders in the elderly at the Posyandu (Integrated Healthcare Center) of Semaka area. Methods: This research was a descriptive correlation and cross-sectional approach. As for the number of respondent in this study were 60 erderly. Results: The results of the Kendall tau test obtained the value of 0.000 with a significant value of 0.389. This showed that the p value was <0.05, this Ha was accepted and Ho was rejected. This meant that there was a correlation between posture changes and static balance disorders in the elderly. Conclusion: There is a correlation between posture changes and the static balance in the elderly at the Posyandu of Semaka area. For health workers in the local health center area to carry out regular counseling on the risk of falling falls by correcting balance disorders in the ederly in order to preventive measures.